DIGITALIZATION AND MEDIA CONVERGENCE IMPLICATION IN THE RADIO BUSINESS WITH WEB DEVELOPMENT AND STREAMING APPLICATIONS - Paradhita, Astrid Noviana; Oktavia , Dinda Ayu (This journal is published by the Vocational School of Universitas Sebelas Maret., 2025)
In the era of digitalization like today, everyone is made easier by various rapidly growing technologies. Information and communication technology development has made analog communication systems adapt and transform into digital information and communication systems. Business industries engaged in information media, such as Radio, are not spared from this phenomenon. Radio can be threatened by the existence of various digital platforms that facilitate public access to information. Therefore, This research was conducted to optimize the broadcasting technology for Radio business to remain in demand by the public. One of the strategies taken by the radio industry is to carry out media convergence. One of the radio businesses that has implemented media convergence is PTPN Radio Solo. The research is carried out by applying research methods that have been designed so that research can be carried out in a structured manner. This research was carried out using a case study research design, data collection through observation and interviews, and qualitative descriptive discussion methods. PTPN Radio Solo has successfully implemented broadcast digitalization using streaming websites and the Noice streaming application. Media convergence has also penetrated social media, which is popular with young people. After implementing media convergence, PTPN Radio Solo can increase its market. The number of clients interested in advertising on PTPN Radio Solo evidences this.